INTERNET OF THINGS (IoT) DESIGN IN RUNWAY EDGE LIGHT TROUBLESHOOTING MONITORING SYSTEM USING THE BLYNK APPLICATION NODEMCU ESP 8266 BASED SMARTPHONES - Pandu Pratama, Kevin; Hariyadi, Slamet; Kosasih, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
IoT or Internet of Think is a concept to expand the benefits of always- connected internet connectivity. Among them are the ability to share data and remote monitoring. One of its applications is used to monitor data on Runway Edge Light. Runway Edge Light is one of the equipment in the Airfield Lighting System (ALS), namely in the form of lights that are on either side of the runway along the runway at the airport. This final project aims to innovate a tool based on making it easier for technicians to monitor trouble source locations or where there are problems with runway edge lights at airports, because of the long distance and the number of lights along the runway at each airport which will be very time-consuming if it has to be investigated one by one when a problem occurs that causes the equipmentto work less than optimally. This final project uses the NodeMCU ESP 8266 as its microcontroller, the data taken from the detection of the failure value of the lamp uses the Pzem-004t current sensor to detect current and the BH1750 light sensor to detect the lumen value of the lamp will then be processed first by NodeMCU ESP 8266 before being sent to the blynk webserver. NodeMCU ESP 8266 sends data to the blynk webserver through the help of a wifi signal. Then the blynk application on the smartphone will display monitoring data from the sensor readings sent by NodeMCU ESP 8266. The research results of this tool only show monitoring the status of the lights on or off from the runway edge light prototype and the lumen on the runway edge light prototype which can be monitored using a smartphone with the help of the blynk application so that with this innovation if implemented it will help technicians’ performance become faster and more efficient. According to system testing, the interface on the smartphone can read the status of the runway edge light on or off during operation along with its lumen value.